Oblicz wartość liczbowa wyrażenia

A -y + 8x - z - 2x dla x= -2 , y=6 , z= -3
b. 9y - ( 7y +x ) +( 6x - 7 y ) dla x= -2 , y= 3

zad 2
usuń nawiasy i wykonaj redukcje wyrazów podobnych

a. ( a+b ) + (2a -b )
b. 2x + (3y - 2z) + ( 3z - 2x)
c. -5ab +(bc - 2ab ) + 4cb
d. ( 5xyz - 2xz ) + (4zx - 7 zyx )

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T15:32:40+01:00
1
a)-y + 8x - z - 2x=6x-y-z=6*(-2)-6-(-3)=-12-6+3=-15
b) 9y - ( 7y +x ) +( 6x - 7 y )= 9y-7y-x+6x-7y=-5y+5x=-5*3+5*(-2)=-15-10=-25

2
a. ( a+b ) + (2a -b )=a+b+2a-b=3a
b. 2x + (3y - 2z) + ( 3z - 2x)= 2x+3y-2z+3z-2x= 3y+z
c. -5ab +(bc - 2ab ) + 4cb= -ab+bc-2ab+4cb=-3ab+5bc
d. ( 5xyz - 2xz ) + (4zx - 7 zyx )= 5xyz-2xz+4zx-7zyx=-2xyz+2xz
1 5 1